2016
DOI: 10.1007/s10265-016-0890-4
|View full text |Cite
|
Sign up to set email alerts
|

Leaf structure affects a plant’s appearance: combined multiple-mechanisms intensify remarkable foliar variegation

Abstract: The presence of foliar variegation challenges perceptions of leaf form and functioning. But variegation is often incorrectly identified and misinterpreted. The striking variegation found in juvenile Blastus cochinchinensis (Melastomataceae) provides an instructive case study of mechanisms and their ecophysiological implications. Variegated (white and green areas, vw and vg) and non-variegated leaves (normal green leaves, ng) of seedlings of Blastus were compared structurally with microtechniques, and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…The analysis of the costs and benefits of leaf variegation has been addressed lately in a series of studies (Wang et al, 2016). In several cases, it has been demonstrated that variegation does not represent a significant cost because of improved light transmission to inner zone of canopies, or even may help plants cope with abiotic stress (Chen et al, 2017). Nevertheless, the presence of important leaf zones almost totally devoid of chlorophyll in variegated plants such as Ficus may lower overall growth, in comparison to totally green genotypes, as shown for oleander (Nerium oleander L.) and willow myrtle (Agonis flexuosa) by Downton and Grant (1994).…”
Section: Light Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the costs and benefits of leaf variegation has been addressed lately in a series of studies (Wang et al, 2016). In several cases, it has been demonstrated that variegation does not represent a significant cost because of improved light transmission to inner zone of canopies, or even may help plants cope with abiotic stress (Chen et al, 2017). Nevertheless, the presence of important leaf zones almost totally devoid of chlorophyll in variegated plants such as Ficus may lower overall growth, in comparison to totally green genotypes, as shown for oleander (Nerium oleander L.) and willow myrtle (Agonis flexuosa) by Downton and Grant (1994).…”
Section: Light Intensitymentioning
confidence: 99%
“…Low light levels may differentially affect green and variegated genotype development (Scuderi et al, 2013). It has been suggested that leaf variegation is a naturally evolved feature that allows light reflection, thus allowing a better illumination in inner canopy zones, at a rather low energetic cost (Chen et al, 2017). According to Konoplyova et al (2008), variegation may be useful under higher light intensities, while on the contrary, dark green leaves (and completely green genotypes) may be more efficiently adapted to low irradiances.…”
Section: Introductionmentioning
confidence: 99%
“…las plantas (Givnish, 1990). Además, serían el resultado de diferentes presiones selectivas que habrían moldeado y orientado estos rasgos, a fin de minimizar los costos de portar hojas y maximizar la ganancia de carbono en la planta (Lev-Yadun, 2016;Chen et al, 2017).…”
Section: Discussionunclassified
“…For example, the silvery appearance of the Leucadendron argenteum leaves is caused by a dense layer of straight, unbranched, and light reflecting trichomes (Barthlott, Mail, Bhushan, & Koch, ). Sometimes the actual appearance of natural colors can be made by combining different color sources depending on plant species (Chen et al, ; Sun et al, ).…”
Section: Inroductionmentioning
confidence: 99%